(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this paper the Design and development of garbage monitoring with bad smell detection is implemented. Basically, Smart waste management and monitoring system plays very important role in present generation. Firstly, when the waste is reached up to 75% then I.R Sensor-1 will be detected and sends an SMS and location of that place to the corresponding officer of that street. In the same way, when the waste is reached above 90% then I.R Sensor-2 will be detected and sends an SMS and location of that place to the corresponding officer of that street. The bad smell detection sensor will detect the bad smell and gives a beep sound using buzzer and in the same way message and location also send to the corresponding officer. Hence this project detects fast and gives effective outcome.